Cultivating Courage to Overcome Bullying Through Diversity Book Clubs - Sonja Ezell (The Advocate, 2018)
As universities enroll increasingly diverse student populations, fill tenure track positions with minority status faculty, and hire staff members conscientiously, they need transformative narratives and culturally sensitive dialogs as adaptive changes. A small university in the Midwest provided a diversity book club to promote weekly conversation among students, faculty, and staff on issues related to race religion, ethnicity, sexuality and gender. This study examines diversity book club study offerings for courageous responses to bullying and recommends practices to cultivate courage to overcome bullying related to diverse populations on university campuses.